PENENTUAN AKUMULASI RADIOFARMAKA Tc99m MDP PADA SPINE DAN STERNUM SAAT PEMERIKSAAN BONE SCAN PASIEN KANKER PAYUDARA - Arifah, Dwi Intan; Setiabudi, Wahyu (BERKALA FISIKA, 2021)
Based on data from Indonesian Health Ministry, breast cancer is the type of cancer with the highest prevalence in Indonesia amounted to 0.5% in 2013. This study aims to determine the accumulation of  activity  Tc99m  Methylene  Diphosponate  (MDP)  on  the  bone  around  the  breast,  spine  and sternum. This study was conducted on 30 patients undergoing the bone scan using in vivo nuclear medicine technique. The study was conducted using Tc99m obtained from elution of Mo99 generator and mixed with MDP. Bone scan was performed by injecting Tc99m MDP intravenously into the patients arm as much 15.84 – 21.95 mCi. Furthermore, the anterior posterior planar imaging in whole of body at 4 hours after injection of the patient by using a gamma camera. Then, using region of interest (ROI), the accumulative of activity on bone can be measured. A range of values based on the activity of bone metastasis can be seen from the percentage uptake of lesions found on the spine  and  sternum.  Based  on  the  existence  of  lesions,  there  were  12  patients  had  lesions  in  the spine only, 9 patients had lesions in the sternum only, 7 patients had lesions on both of them and there are 16 patients who have not lesions in both.